Location of the H[+/-] level: Experimental limits for muonium - Lichti, R. L. (2006)
The defect energy levels for muonium, a light pseudo-isotope of hydrogen, are investigated to define the equivalent of the H[+/-] level which is predicted to be fixed at a universal energy. Existing results for Mu at donor and acceptor sites in silicon tentatively place Mu[+/-] approximately 0.5 eV above the predicted hydrogen level. Measured donor ionization energies in other materials in which two neutral Mu centers are observed define a range for the Mu acceptor energies. We discuss possible reinterpretation of known energies and the current state of investigations to obtain these muonium acceptor levels in order to further refine a determination of the Mu[+/-] energy.